Porous ceramic loaded three-dimensional molybdenum disulfide composite catalytic material and preparation method thereof

The nanoflower spherical molybdenum disulfide was prepared by hydrothermal method and combined with silicon carbide porous ceramics, which solved the problem of insufficient performance of MoS2 photocatalytic materials in the prior art, and prepared composite catalytic materials with high-efficiency photocatalytic properties, good thermal conductivity and low cost, achieving the effect of efficient catalytic reactions.

CN119869579APending Publication Date: 2025-04-25DONGGUAN XY PRECISION TUNGSTEN CARBIDE CO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510099288.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, there are few reports on the construction of heterojunctions using MoS2 as a material and constructing composite materials with high-efficiency photocatalytic properties, and there are some defects in the preparation of nano-scale spherical molybdenum disulfide, which affects its use efficiency.

Method used

Nanoflower spherical molybdenum disulfide powder was prepared by hydrothermal method, and combined with silicon carbide porous ceramics with different ratios to prepare porous ceramics with three-dimensional molybdenum disulfide composite catalytic material. The method includes steps such as raw material mixing, hydrothermal reaction, centrifugation and washing, drying, and glue preparation and loading.

Benefits of technology

The prepared composite catalytic material has the outstanding advantages of good thermal conductivity, excellent catalytic activity and low cost. It can show high activity, high selectivity and high energy utilization efficiency in catalytic reactions. The catalytic degradation experiments were 3-5 times, and the degradation rate of organic matter was still above 60-70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869579A_ABST
    Figure CN119869579A_ABST
Patent Text Reader

Abstract

The invention relates to the field of nano catalytic materials, and discloses a porous ceramic loaded three-dimensional molybdenum disulfide composite catalytic material and a preparation method thereof. The composite catalytic material disclosed by the invention is prepared from the nano flower-ball-shaped molybdenum disulfide powder prepared by a hydrothermal method and the nano flower-ball-shaped molybdenum disulfide and the porous ceramic according to different proportions, and the prepared composite catalytic material has the outstanding advantages of good thermal conductivity, excellent catalytic activity and low cost; the practical application requirements in the catalytic reaction field can be met. The preparation method disclosed by the invention is simple, easy for mass production, high in organic matter degradation rate and low in cost, and can meet the actual application requirements in the field of catalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite catalytic materials, and more specifically, to a porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material and a preparation method thereof. Background Art

[0002] Porous ceramics occupy an important position in the field of catalyst carriers due to their excellent mechanical properties, thermophysical properties and chemical stability; while molybdenum disulfide (MoS2) has become one of the emerging photocatalytic materials due to its unique photoelectric properties and catalytic stability.

[0003] MoS2 has a layered structure similar to graphite. Due to its anisotropic structural characteristics, MoS2 is easy to form two-dimensional nanosheets. Since scattered nanosheets are prone to stacking or overlapping when used, their available specific surface area is greatly reduced. Studies have shown that MoS2 nanosheets can be organized into a three-dimensional flower-like porous structure in a certain way, which not only has a larger specific surface area and more channels for ion transfer, but also has better structural stability.

[0004] However, there are few reports in the prior art on constructing heterojunctions using MoS2 as the material and building composite materials with high-efficiency photocatalytic properties.

[0005] The present invention combines the structural advantages and functional properties of porous ceramics with MoS2 to construct a new composite material with high-efficiency photocatalytic performance, which is expected to promote the further development of semiconductor photocatalytic technology and provide new solutions for energy conversion and environmental governance. Summary of the invention

[0006] The purpose of the present invention is to address some defects in the preparation of nano-flower-shaped molybdenum disulfide in the prior art and to improve its use efficiency. The present invention uses a nano-flower-shaped molybdenum disulfide powder prepared by a hydrothermal method, and then prepares the composite catalytic material of the present invention by different ratios of nano-flower-shaped molybdenum disulfide and silicon carbide porous ceramics. The prepared composite catalytic material has the outstanding advantages of good thermal conductivity (thermal conductivity coefficient is 100-130w / mk), excellent catalytic activity (after 3-5 cycles of catalytic degradation experiments, the degradation rate of organic matter is still more than 60-70%), and low cost (the preparation process is simple and can be mass-produced), which can meet its actual application needs in the field of catalytic reactions.

[0007] The present invention provides a method for preparing a porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material, comprising the following steps:

[0008] Step (1) Preparation of nano-flower spherical molybdenum disulfide (MoS2):

[0009] Step (1.1) raw material mixing: weigh thioacetamide and sodium molybdate according to a sulfur-molybdenum molar ratio of 2.5-3:1-1.1 and pour them into a beaker, add 50-80 mL of deionized water to the beaker, and stir magnetically at room temperature until they are completely dissolved and the solution is colorless and transparent;

[0010] Step (1.2) hydrothermal reaction: pour the dissolved mixed solution into a reactor, with the solution occupying 2 / 3 of the reactor, and perform a hydrothermal reaction at 180-240° C.;

[0011] Step (1.3) Centrifugation and washing: After the hydrothermal reaction is completed, wait until the temperature drops to room temperature, take out the mixed solution and pour it into centrifuge tubes respectively, centrifuge it with a centrifuge, suck out the supernatant with a rubber-tipped dropper, pour deionized water into the centrifuge tube, perform ultrasonic treatment, and then centrifuge it. Repeat the above steps at least 3 times by alternating washing and centrifugation with deionized water and anhydrous ethanol, pour the washed and centrifuged sample into a glass evaporating dish and dry it in a drying oven at 60-80°C for 10-12h; ensure that the sample is fully cleaned to ensure the quality of the finished product;

[0012] In step (1.4), collect the dried black powder and label it for later use.

[0013] Step (2) Preparation of porous ceramic-supported nano-flower spherical molybdenum disulfide:

[0014] Step (2.1) Preparation of adhesive: Based on the molybdenum disulfide prepared above, maleic acid is weighed and poured into a beaker according to a molar ratio of MoS2 to maleic acid of 1:4-6 (preferably 1:5), 30 mL of anhydrous ethanol is added to the beaker, and magnetic stirring is performed at room temperature until it is completely dissolved to obtain an organic adhesive;

[0015] The organic adhesive of this scheme is mainly reflected in the loading process. The flower-ball-shaped molybdenum disulfide prepared in this application does not agglomerate, but is dispersedly attached to the porous silicon carbide ceramic substrate, which shows that the organic adhesive under this ratio is more suitable.

[0016] Step (2.2) Loading: Weigh 5 groups according to the mass ratio of molybdenum disulfide to silicon carbide porous ceramic powder of 1:1, 1:2, 1:3, 2:1, and 3:1, respectively, dissolve the weighed molybdenum disulfide in 70 mL of anhydrous ethanol, add the organic binder prepared above after ultrasonic dispersion for 2-4 hours, and continue ultrasonic treatment for 1-2 hours to obtain a nano-flower spherical molybdenum disulfide dispersion;

[0017] Silicon carbide porous ceramic powders with a porosity of 10-70% were added to the dispersion according to the above ratio, numbered 1-1, 1-2, 1-3, 2-1, and 3-1 respectively, and dried under magnetic stirring at 80-100° C. to obtain a silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0018] Preferably, the porous ceramic powder is a silicon carbide porous ceramic powder with a porosity of 30-40%. The greater the porosity, the greater the specific surface area for molybdenum disulfide to attach, and the better the catalytic effect. At present, the porous ceramic powder prepared by our company has a porosity of about 30-40%, with good catalytic effect and low material cost.

[0019] Preferably, in the step (1.1), the sulfur-molybdenum molar ratio is 2.66:1.03, and the amount of deionized water is 60 mL. The molybdenum disulfide prepared by selecting the specific sulfur-molybdenum molar ratio (2.66:1.03) has uniform morphology and excellent performance.

[0020] Preferably, the step (1.2) is specifically to pour the dissolved mixed solution into a stainless steel high-pressure reactor lined with polytetrafluoroethylene, with the solution accounting for 2 / 3 of the reactor, and perform a hydrothermal reaction in an electric heated blast drying oven at 180-240° C. for 16-24 hours. Specifically, in the hydrothermal reaction, the preferred reaction temperature is 200° C. and the reaction time is 16 hours.

[0021] Preferably, the centrifugation and washing in step (1.3) are specifically as follows: after the hydrothermal reaction is completed, wait until the temperature drops to room temperature, take out the mixed solution, pour it into 10mL centrifuge tubes respectively, fill each tube with 9mL of solution, centrifuge at 80-90r / min, centrifuge for 3min, suck out the supernatant with a rubber-tipped dropper and pour it into a waste liquid tank, pour deionized water into the test tube to 9mL, perform ultrasonic treatment for 3-5min, and then centrifuge, wash and centrifuge with deionized water and anhydrous ethanol alternately, repeat the above steps 5 to 8 times, pour the washed and centrifuged sample into a glass evaporating dish and dry it in an electric blast drying oven at 60-80°C for 10-12h. More preferably, the drying temperature of the electric blast drying oven is preferably 76-80°C.

[0022] Preferably, in step (1), the molybdenum source is at least one of sodium molybdate, ammonium molybdate and ammonium heptamolybdate, and the sulfur source is at least one of thiourea and thioacetamide.

[0023] Preferably, the molybdenum disulfide obtained in step (1) has a bandgap of 1.37-1.56 eV as measured by solid ultraviolet light.

[0024] A porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material is prepared by the method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material. The silicon carbide porous ceramic-supported nano-spherical molybdenum disulfide composite catalytic material has a bandgap of 1.67-1.83 eV and a thermal conductivity of 100-130 w / mk. The electron-vacancy recombination rate is effectively reduced, and the redox properties of the composite catalyst are improved.

[0025] The porous ceramic-loaded three-dimensional molybdenum disulfide composite catalytic material of the present invention is used for the degradation of organic matter such as rhodamine B, methylene blue, methyl orange and antibiotics. After 3-5 cycles of catalytic degradation experiments, the degradation rate of the organic matter is still above 60%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The silicon carbide porous ceramic loaded nano-spherical molybdenum disulfide composite catalytic material prepared by the present invention has a simple preparation method and is easy to produce in large quantities. It can reduce economic costs when applied to actual production. For example, when applied to the field of photocatalysis, the energy driving force is solar energy, which is not only green and environmentally friendly but also does not cause energy waste.

[0028] 2. The silicon carbide porous ceramic loaded with nano-flower spherical molybdenum disulfide prepared by the present invention can provide a larger specific surface area (19.7357-30.1199m 2 / g), has good intrapore diffusion performance, and has high activity, high selectivity and high energy utilization efficiency in catalytic reactions.

[0029] 3. The silicon carbide porous ceramic loaded nano-spherical molybdenum disulfide composite catalytic material prepared by the present invention has high wear resistance (due to the high lubricity of molybdenum disulfide, the wear resistance of the composite material is increased), acid and alkali corrosion resistance, can withstand high temperature (the maximum long-term use temperature is 1200°C), high pressure, and is made of a relatively light material such as a three-way catalytic converter for automobile exhaust treatment (common porous catalytic ceramic carrier materials are aluminum oxide, silicon carbide, titanium dioxide, etc., but silicon carbide (3.1g / cm 3 ) compared to alumina (3.9 g / cm 3 ) has a lower density than other materials, so it is lighter to make a three-way catalyst).

[0030] 4. The preparation method of the present invention is simple, and the reactants are only sodium molybdate and thioacetamide. The prepared molybdenum disulfide flower balls are uniform in size, with a flower piece of 1-5nm and a ball diameter of 300-380nm. It is not easy to agglomerate, and the flower piece shape is obvious. The band gap width is 1.37-1.56eV using solid ultraviolet testing, and the performance is excellent.

[0031] 5. The composite catalytic material prepared by the present invention has the outstanding advantages of good thermal conductivity (thermal conductivity coefficient is 100-130w / mk), excellent catalytic activity (after 3-5 cycles of catalytic degradation experiments, the degradation rate of organic matter is still more than 60-70%), and low cost (simple preparation process and mass production can be achieved), which can meet the practical application needs in the field of catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0033] Figure 1 This is the XRD diagram of molybdenum disulfide of the present invention.

[0034] Figure 2 This is the XRD diagram of the MoS2 / SiC composite catalytic material of the present invention.

[0035] Figure 3 This is the SEM image of molybdenum disulfide of the present invention.

[0036] Figure 4 This is the SEM image of the MoS2 / SiC composite catalytic material of the present invention. DETAILED DESCRIPTION

[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. In the following embodiments, if there is no special description of the raw materials or processing technology, it is indicated that the conventional commercially available raw material products or conventional processing technologies used are all in the art.

[0038] Figure 1 to Figure 2 The XRD diagram of the nano-scale flower-shaped molybdenum disulfide and silicon carbide porous ceramic-loaded nano-spherical molybdenum disulfide composite catalyst prepared in this scheme. The photocatalytic reaction under natural conditions is simulated indoors. A xenon lamp can be used to simulate sunlight. Organic pollutants can be selected from rhodamine B, methyl orange, methylene blue and antibiotics. Figure 1 It can be seen that the molybdenum disulfide flower balls prepared by the present invention are uniform in size, not easy to agglomerate, have obvious flower flakes, and have excellent performance.

[0039] Figure 3 Under scanning electron microscope observation, the flower pieces are 1-5nm in size, the sphere diameter is 300-380nm, the spheres are uniform in size, the flower pieces are obvious, and there is no agglomeration.

[0040] Figure 4 Under the scanning electron microscope, the microscopic morphology is that molybdenum disulfide is attached to the silicon carbide porous ceramic to form a heterojunction, and the two are evenly bonded. The organic adhesive in this scheme is mainly reflected in the loading process. Figure 4 It can be seen that the flower-shaped molybdenum disulfide did not agglomerate, but was dispersedly attached to the porous silicon carbide ceramic matrix, indicating that the organic adhesive under this ratio is more suitable.

[0041] Example 1

[0042] A method for preparing a porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to this embodiment comprises the following steps:

[0043] Step (1) Preparation of nano-flower spherical molybdenum disulfide:

[0044] Step (1.1) Raw material mixing: Weigh thioacetamide and sodium molybdate according to a sulfur-molybdenum molar ratio of 2.66:1.03 and pour them into a beaker, add 60 mL of deionized water to the beaker, and stir magnetically until completely dissolved;

[0045] Step (1.2) hydrothermal reaction: pour the dissolved mixed solution into a stainless steel high-pressure reactor lined with polytetrafluoroethylene, with the solution accounting for 2 / 3 of the reactor, and perform hydrothermal reaction in an electric heated air drying oven at 180-240° C. for 16-24 hours;

[0046] Step (1.3) Centrifugation and washing: After the hydrothermal reaction is completed, wait until the temperature drops to room temperature, take out the mixed solution, pour it into 10mL centrifuge tubes, fill each tube with 9mL of solution, centrifuge at 80-90r / min, centrifuge for 3min, suck out the supernatant with a rubber-tipped dropper and pour it into a waste liquid tank, then pour deionized water into the test tube to 9mL, perform ultrasonic treatment for 3-5min, and then centrifuge again, wash and centrifuge alternately with deionized water and anhydrous ethanol, repeat the above steps 5 to 8 times, pour the washed and centrifuged samples into a glass evaporating dish and dry them in an electric heated blast drying oven at 60-80℃ for 10-12h;

[0047] Step (1.4) Collection: Collect the dried black powder and label it for later use.

[0048] Step (2) Preparation of porous ceramic-supported nano-flower spherical molybdenum disulfide:

[0049] Step (2.1) Preparation of adhesive: According to the molybdenum disulfide prepared above, maleic acid is weighed and poured into a beaker at a molar ratio of MoS2 to maleic acid of 1:5, 30 mL of anhydrous ethanol is added to the beaker, and magnetic stirring is performed until it is completely dissolved to obtain an organic adhesive;

[0050] Step (2.2) Loading: Molybdenum disulfide and silicon carbide porous ceramic powder are weighed according to a mass ratio of 1:1, and the weighed molybdenum disulfide is dissolved in 70 mL of anhydrous ethanol. After ultrasonic dispersion for 2-4 hours, the organic binder prepared above is added, and ultrasonic treatment is continued for 1-2 hours to obtain a nano-flower spherical molybdenum disulfide dispersion;

[0051] According to the above ratio, silicon carbide porous ceramic powder with a porosity of 30% is added to the dispersion, numbered 1-1, and dried at 80-100° C. with magnetic stirring to obtain a silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that: in step (2.2) of this embodiment, loading is as follows: weighing molybdenum disulfide and alumina porous ceramic powder according to a mass ratio of 1:2, dissolving the weighed molybdenum disulfide in 70 mL of anhydrous ethanol, adding the organic binder prepared above after ultrasonic dispersion for 2-4 hours, and continuing ultrasonic treatment for 1-2 hours to obtain a nano-flower-shaped molybdenum disulfide dispersion;

[0054] According to the above ratio, alumina porous ceramic powder with a porosity of 40% is added to the dispersion, numbered 1-2, and dried at 80-100° C. with magnetic stirring to obtain alumina porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0055] The rest of the contents of this embodiment are the same as those of Embodiment 1 and will not be described again here.

[0056] Example 3

[0057] The difference between this embodiment and embodiment 1 is that: in step (2.2) of this embodiment, loading is as follows: weighing molybdenum disulfide and titanium dioxide porous ceramic powder according to a mass ratio of 1:3, dissolving the weighed molybdenum disulfide in 70 mL of anhydrous ethanol, adding the organic binder prepared above after ultrasonic dispersion for 2-4 hours, and continuing ultrasonic treatment for 1-2 hours to obtain a nano-flower-shaped molybdenum disulfide dispersion;

[0058] According to the above ratio, titanium dioxide porous ceramic powder with a porosity of 60% is added to the dispersion, numbered 1-3, and dried under magnetic stirring at 80-100° C. to obtain a titanium dioxide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0059] The rest of the contents of this embodiment are the same as those of Embodiment 1 and will not be described again here.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that: in step (2.2) of this embodiment, loading is as follows: weighing molybdenum disulfide and silicon carbide porous ceramic powder according to a mass ratio of 2:1, dissolving the weighed molybdenum disulfide in 70 mL of anhydrous ethanol, adding the organic binder prepared above after ultrasonic dispersion for 2-4 hours, and continuing ultrasonic treatment for 1-2 hours to obtain a nano-flower-shaped molybdenum disulfide dispersion;

[0062] According to the above ratio, silicon carbide porous ceramic powder with a porosity of 30-40% is added to the dispersion, numbered 2-1, and dried at 80-100° C. with magnetic stirring to obtain a silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0063] The rest of the contents of this embodiment are the same as those of Embodiment 1 and will not be described again here.

[0064] Example 5

[0065] The difference between this embodiment and embodiment 1 is that: in step (2.2) of this embodiment, loading is as follows: weighing molybdenum disulfide and silicon carbide porous ceramic powder according to a mass ratio of 3:1, dissolving the weighed molybdenum disulfide in 70 mL of anhydrous ethanol, adding the organic binder prepared above after ultrasonic dispersion for 2-4 hours, and continuing ultrasonic treatment for 1-2 hours to obtain a nano-flower-shaped molybdenum disulfide dispersion;

[0066] According to the above ratio, silicon carbide porous ceramic powder with a porosity of 70% is added to the dispersion, numbered 3-1, and dried at 80-100° C. with magnetic stirring to obtain a silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst.

[0067] The rest of the contents of this embodiment are the same as those of Embodiment 1 and will not be described again here.

[0068] Application Example 1

[0069] 10 g of the above-mentioned silicon carbide porous ceramic-supported nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 1:1 was placed in 50 mL of 20% methyl orange solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance value of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of methyl orange by the composite catalyst under this ratio was about 66.5%.

[0070] Application Example 2

[0071] 10 g of the above-mentioned alumina porous ceramic-loaded nanoflower spherical molybdenum disulfide composite catalyst with a molybdenum disulfide and alumina ratio of 1:2 was added to 50 mL of rhodamine B with a concentration of 20%, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes. After 6 times, a UV-visible spectrophotometer was used to test the absorbance value of the reaction solution. The data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for rhodamine B under this ratio was about 63.2%.

[0072] Application Example 3

[0073] 10 g of the above-mentioned titanium dioxide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst with a molybdenum disulfide and titanium dioxide ratio of 1:3 was placed in 50 mL of an antibiotic solution with a concentration of 20%, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for antibiotics under this ratio was about 76.9%.

[0074] Application Example 4

[0075] 10 g of the above-mentioned silicon carbide porous ceramic-supported nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 2:1 was placed in 50 mL of 20% methyl orange solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance value of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of methyl orange by the composite catalyst under this ratio was about 84.3%.

[0076] Application Example 5

[0077] 10 g of the above-mentioned silicon carbide porous ceramic-supported nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 3:1 was placed in 50 mL of 20% methyl orange solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance value of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of methyl orange by the composite catalyst under this ratio was about 72.7%.

[0078] Application Example 6

[0079] 10 g of the above-mentioned silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 1:1 was placed in 50 mL of a 20% methylene blue solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for methylene blue under this ratio was about 63.7%.

[0080] Application Example 7

[0081] 10 g of the above-mentioned alumina porous ceramic-loaded nanoflower spherical molybdenum disulfide composite catalyst with a molybdenum disulfide and alumina ratio of 1:2 was placed in 50 mL of an antibiotic solution with a concentration of 20%, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination was started, and a xenon lamp was used to simulate sunlight. 3 mL of the reaction solution was taken every 30 minutes, and it was taken 6 times. Then, an ultraviolet-visible spectrophotometer was used to test the absorbance value of the reaction solution, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for antibiotics under this ratio was about 63.8%.

[0082] Application Example 8

[0083] 10g of the above-mentioned titanium dioxide porous ceramic supported nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to titanium dioxide of 1:3 was placed in 50mL of a 20% rhodamine B solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3mL of the reaction solution was taken. Illumination was started, and a xenon lamp was used to simulate sunlight. 3mL of the reaction solution was taken every 30 minutes, and it was taken 6 times. Then, an ultraviolet-visible spectrophotometer was used to test the absorbance value of the reaction solution, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for rhodamine B under this ratio was about 81.2%.

[0084] Application Example 9

[0085] 10 g of the above-mentioned silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 2:1 was placed in 50 mL of a 20% methylene blue solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3 mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3 mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for methylene blue under this ratio was about 77.2%.

[0086] Application Example 10

[0087] 10g of the above-mentioned silicon carbide porous ceramic-loaded nano-flower spherical molybdenum disulfide composite catalyst with a ratio of molybdenum disulfide to silicon carbide of 3:1 was placed in 50mL of a 20% methylene blue solution, and after ultrasonic treatment for 3 minutes, it was placed in a photochemical reaction instrument to establish adsorption-desorption equilibrium, and then 3mL of the reaction solution was taken. Illumination began, using a xenon lamp to simulate sunlight, and 3mL of the reaction solution was taken every 30 minutes for 6 times. The absorbance of the reaction solution was tested using an ultraviolet-visible spectrophotometer, and the data was analyzed to evaluate the decomposition rate of the catalyst for organic pollutants. The degradation rate of the composite catalyst for methylene blue was about 68% under this ratio.

[0088] The beneficial effects of the above implementation method are as follows: the preparation method of the present invention is simple, the prepared molybdenum disulfide flower spheres are uniform in size, the flower pieces are 1-5nm, the ball diameter is 300-380nm, it is not easy to agglomerate, the flower pieces are obvious, and the band gap width is 1.37-1.56eV using solid ultraviolet testing, and the performance is excellent; the composite catalytic material formed by the silicon carbide porous ceramic loaded with nano-spherical molybdenum disulfide has high wear resistance, acid and alkali corrosion resistance, can withstand high temperature (the maximum long-term use temperature is 1200°C) and high pressure, has good thermal conductivity (thermal conductivity coefficient is 100-130w / mk), and can provide a large specific surface area (19.7357-30.1199m2 / g), has good intrapore diffusion performance, high activity, high selectivity and high energy utilization efficiency in catalytic reactions, and the degradation rate of organic matter is still above 60-70% after 3-5 cycles of catalytic degradation experiments, with the highest degradation rate reaching 84.33%.

[0089] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material, characterized in that: The following steps are involved: Step (1) Preparation of nano-flower spherical molybdenum disulfide: Step (1.1) raw material mixing: weigh thioacetamide and sodium molybdate according to a sulfur-molybdenum molar ratio of 2.5-3:1-1.1 and pour them into a beaker, add 50-80 mL of deionized water to the beaker, and stir magnetically until completely dissolved; Step (1.2) hydrothermal reaction: pour the dissolved mixed solution into a reactor, with the solution occupying 2 / 3 of the reactor, and perform a hydrothermal reaction; Step (1.3) Centrifugation and washing: After the hydrothermal reaction is completed, wait until the temperature drops to room temperature, take out the mixed solution and pour it into centrifuge tubes respectively, centrifuge it with a centrifuge, suck out the supernatant with a rubber-tipped dropper, pour deionized water into the centrifuge tube, perform ultrasonic treatment, and then centrifuge it. Repeat the above steps at least 3 times by alternating washing and centrifugation with deionized water and anhydrous ethanol, pour the washed and centrifuged sample into a glass evaporating dish and dry it in a drying oven at 60-80°C for 10-12h; Step (1.4) collect the dried powder for later use; Step (2) Preparation of porous ceramic-supported nano-flower spherical molybdenum disulfide: Step (2.1) Preparation of adhesive: Based on the molybdenum disulfide prepared above, maleic acid is weighed and poured into a beaker according to a molar ratio of MoS2 to maleic acid of 1:4-6, anhydrous ethanol is added to the beaker, and magnetic stirring is performed until it is completely dissolved to obtain an organic adhesive; Step (2.2) Loading: Molybdenum disulfide and porous ceramic powder are weighed according to a mass ratio of 1-3:1-3, and the weighed molybdenum disulfide is dissolved in anhydrous ethanol, and the organic binder prepared above is added after ultrasonic dispersion, and the ultrasonic treatment is continued to obtain a nano-flower spherical molybdenum disulfide dispersion; Porous ceramic powders with a porosity of 10-70% are added to the dispersion according to the above ratio, and the mixture is dried by magnetic stirring to obtain a porous ceramic-loaded nano-flower-shaped molybdenum disulfide composite catalyst.

2. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: In the step (1.1), the sulfur-molybdenum molar ratio is 2.66:1.03, and the amount of deionized water is 60 mL.

3. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: The step (1.2) is specifically to pour the dissolved mixed solution into a stainless steel high-pressure reactor lined with polytetrafluoroethylene, with the solution accounting for 2 / 3 of the reactor, and perform a hydrothermal reaction in an electric heated blast drying oven at 180-240° C. for 16-24 hours.

4. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: The step (1.3) of centrifugation and washing is specifically as follows: after the hydrothermal reaction is completed, wait until the temperature drops to room temperature, take out the mixed solution, pour it into 10mL centrifuge tubes respectively, fill each tube with 9mL of solution, use a centrifuge at 80-90r / min, centrifuge for 3min, suck out the supernatant with a rubber-tipped dropper and pour it into a waste liquid tank, then pour deionized water into the test tube to 9mL, perform ultrasonic treatment for 3-5min, and then centrifuge, wash and centrifuge alternately with deionized water and anhydrous ethanol, repeat the above steps 5 to 8 times, pour the washed and centrifuged sample into a glass evaporating dish and dry it in an electric heated forced air drying oven at 60-80°C for 10-12h.

5. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: In the step (1), the molybdenum source is at least one of sodium molybdate, ammonium molybdate and ammonium heptamolybdate, and the sulfur source is at least one of thiourea and thioacetamide.

6. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: In the step (2), the porous ceramic powder is silicon carbide, titanium dioxide, or alumina porous ceramic powder.

7. The method for preparing the porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material according to claim 1, characterized in that: The molybdenum disulfide obtained in step (1) has a bandgap of 1.37-1.56 eV using solid ultraviolet testing.

8. A porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material, characterized in that: The porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material is prepared by the preparation method of any one of claims 1 to 7. The silicon carbide porous ceramic-supported nano-spherical molybdenum disulfide composite catalytic material has a band gap of 1.67-1.83 eV and a thermal conductivity of 100-130 w / mk.

9. A porous ceramic-supported three-dimensional molybdenum disulfide composite catalytic material as described in claim 8 is used for the degradation of organic matter such as rhodamine B, methylene blue, methyl orange, and antibiotics. After 3-5 cycles of catalytic degradation experiments, the degradation rate of the organic matter is still above 60%.

Citation Information

Cited By

  • Calcium oxide / water foaming type porous ceramic as well as preparation method and application thereof

    CN121293005A